Pengaruh profitabilitas, ukuran perusahaan, dan kebijakan dividen terhadap nilai perusahaan - Sakinah, Irnawati; Hendrani, Ai (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the effect of profitability, firm size and dividend policy on firm value in the consumer goods industry sector. The sample used in this study is the consumer goods industrial sector companies listed on the Indonesia Stock Exchange for the period 2018-2021. The population in this study were 74 companies. The sample in this study was selected using a purposive sampling method with predetermined criteria so that 20 companies can be collected with a total of 80 financial statements. The type of data is secondary data sourced from financial reports and annual reports. The data analysis method used in this study is the classical assumption test, the coefficient of determination (R2) test, multiple linear regression, and hypothesis testing using multiple linear analysis. The results of this study indicate that simultaneously profitability, firm size and dividend policy affect firm value. Partially, profitability has a positive effect on firm value, partially firm size has no effect on firm value and partially dividend policy has no effect on firm value.